A comparison of three different VMAT techniques for the delivery of lung stereotactic ablative radiation therapy. Issue 1 (20th January 2016) - Fitzgerald, Rhys; Owen, Rebecca; Hargrave, Catriona; Pryor, David; Barry, Tamara; Lehman, Margot; Bernard, Anne; Mai, Tao; Seshadri, Venkatakrishnan; Fielding, Andrew
Abstract : A study comparing three different volumetric modulated arc therapy delivery techniques to treat early stage peripheral lung cancer was designed. A beam arrangement consisting of non‐coplanar treatment angles provided best compliance with RTOG lung stereotactic ablative radiation therapy protocols. Abstract: Introduction: The purpose of this study was to investigate coplanar and non‐coplanar volumetric modulated arc therapy (VMAT) delivery techniques for stereotactic ablative radiation therapy (SABR) to the lung. Methods: For ten patients who had already completed a course of radiation therapy for early stage lung cancer, three new SABR treatment plans were created using (1) a coplanar full arc (FA) technique, (2) a coplanar partial arc technique (PA) and (3) a non‐coplanar technique utilising three partial arcs (NCA). These plans were evaluated using planning target volume (PTV) coverage, dose to organs at risk, and high and intermediate dose constraints as incorporated by radiation therapy oncology group (RTOG) 1021. Results: When the FA and PA techniques were compared to the NCA technique, on average the PTV coverage ( V 54Gy ) was similar ( P = 0.15); FA (95.1%), PA (95.11%) and NCA (95.71%). The NCA resulted in a better conformity index (CI) of the prescription dose (0.89) when compared to the FA technique (0.88, P = 0.23) and the PA technique (0.83, P = 0.06). The NCA technique improved the intermediate dose constraints with a statistically significant difference for the D 2cm and R 50% when compared with the FA ( P < 0.03 and <0.0001) and PA ( P < 0.04 and <0.0001) techniques. The NCA technique reduced the maximum spinal cord dose by 2.72 and 4.2 Gy when compared to the PA and FA techniques respectively. Mean lung doses were 4.09, 4.31 and 3.98 Gy for the FA, PA and NCA techniques respectively. Conclusion: The NCA VMAT technique provided the highest compliance to RTOG 1021 when compared to coplanar techniques for lung SABR. However, single FA coplanar VMAT was suitable for 70% of patients when minor deviations to both the intermediate dose and organ at risk (OAR) constraints were accepted.